2017
DOI: 10.1002/14651858.cd010443.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Combined diet and exercise interventions for preventing gestational diabetes mellitus

Abstract: Analysis 1.4. Comparison 1 Combined diet and exercise interventions versus standard care, Outcome 4 Caesarean section....... Analysis 1.5. Comparison 1 Combined diet and exercise interventions versus standard care, Outcome 5 Perinatal mortality....... Analysis 1.6. Comparison 1 Combined diet and exercise interventions versus standard care, Outcome 6 Large-for-gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
207
1
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(250 citation statements)
references
References 161 publications
(5 reference statements)
11
207
1
16
Order By: Relevance
“…Results of this meta‐analysis are consistent with those of previously published meta‐analyses estimating the effect of behavioural interventions in pregnancy on PPWR, as a secondary outcome . These meta‐analyses included data from three to seven included trials.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Results of this meta‐analysis are consistent with those of previously published meta‐analyses estimating the effect of behavioural interventions in pregnancy on PPWR, as a secondary outcome . These meta‐analyses included data from three to seven included trials.…”
Section: Discussionsupporting
confidence: 84%
“…Results of this meta‐analysis are consistent with those of previously published meta‐analyses estimating the effect of behavioural interventions in pregnancy on PPWR, as a secondary outcome . These meta‐analyses included data from three to seven included trials. Agha et al and Bain et al reported similar estimates for the mean difference (MD) in PPWR between groups (MD: −0.99 kg, 95% CI: −2.25 to 0.26 and average MD: −0.72 kg, 95% CI −1.96 to 0.51, respectively) for all follow‐up lengths.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings go in hand with Shepherd et al (35) who detected reduced risk of GDM with their proposed diet and exercise interventions for pregnant women versus women received no intervention. Also, Pan et al (36) reported that women with GDM were older and had higher BMI than women free of GDM and Li et al (37) found the levels of FBG, PPBGG, FSI, lipid profile and HOMA-IR score were significantly higher in GDM than in normal glucose tolerance women with a positive correlation between HOMA-IR and BMI and concluded that with the increases of FBG, the progression of IR is increased and pancreatic β-cell function progressively declines.…”
Section: Discussion:-mentioning
confidence: 82%
“…It is also recommended to continue or initiate moderate‐intensity exercise . Recent meta‐analyses on the effects of diet and exercise interventions in pregnancy reported on benefits in reducing gestational weight gain and GDM. Furthermore, exercise interventions in pregnant women diagnosed with GDM are associated with reduced fasting and postprandial blood glucose concentration .…”
Section: Introductionmentioning
confidence: 99%